Detrimental Effects of Centrally Administered Angiotensin II are Enhanced in a Mouse Model of Alzheimer Disease Independently of Blood Pressure - Koki Takane; Yu Hasegawa; Bowen Lin; Nobutaka Koibuchi; Cheng Cao; Takashi Yokoo; Shokei Kim‐Mitsuyama (Journal of the American Heart Association: Cardiovascular and Cerebrovascular Disease, 2017)
BackgroundThe significance of brain angiotensin II in Alzheimer disease (AD) is unclear. Methods and ResultsTo examine the role of brain angiotensin II in AD, intracerebroventricular angiotensin II infusion was performed on 5XFAD mice, a mouse model of AD, and wild‐type mice, and the detrimental effects of brain angiotensin II was compared between the 2 strains of mice. Intracerebroventricular angiotensin II infusion significantly impaired cognitive function in 5XFAD mice but not in wild‐type mice. This vulnerability of 5XFAD mice to brain angiotensin II was associated with enhancement of hippocampal inflammation and oxidative stress and with increased cerebrovascular amyloid β deposition. We also compared the effect of brain angiotensin II on the heart and skeletal muscle between the 2 strains because AD is associated with heart failure and sarcopenia. We found that cardiac compensatory response of 5XFAD mice to brain angiotensin II–induced hypertension was less than that of wild‐type mice. Brain angiotensin II caused skeletal muscle atrophy and injury in 5XFAD mice more than in wild‐type mice. ConclusionsBrain angiotensin II seems to be involved in cognitive impairment and brain injury in AD, which is associated with oxidative stress, inflammation, and cerebral amyloid angiopathy. Further, brain angiotensin II may participate in cardiac disease and sarcopenia observed in AD.